If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.3z + -2.3z + 0.4 = -7.2 Reorder the terms: 0.4 + 3.3z + -2.3z = -7.2 Combine like terms: 3.3z + -2.3z = 1z 0.4 + 1z = -7.2 Solving 0.4 + 1z = -7.2 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-0.4' to each side of the equation. 0.4 + -0.4 + 1z = -7.2 + -0.4 Combine like terms: 0.4 + -0.4 = 0.0 0.0 + 1z = -7.2 + -0.4 1z = -7.2 + -0.4 Combine like terms: -7.2 + -0.4 = -7.6 1z = -7.6 Divide each side by '1'. z = -7.6 Simplifying z = -7.6
| (4-2i)(6-5i)=0 | | -33=3(4c+5) | | (x+5)2=16x | | x+2(49)=115 | | (5y+2)(3y-1)= | | 3(2x-1)+4=y+25 | | x(x)=1525 | | (x^2)+(18x)+(90)=0 | | 2.5(x-3.6)=x(1.6) | | n+10=3n-10 | | F=3.14msquaredx | | Y=5E+07x+3E+08 | | -(7x-2y-3)= | | 6x=277+3x | | F=3.14msguaredx | | 2(3x-3)=-9 | | (2n-4)-(4n-3)=a | | 5x^2=128 | | 3x^2=15x+42 | | 6.8y-5.8y-9.1=8.4+9.5 | | (-3i)(7i)(-i)=0 | | -1=5x+4 | | X^2-7x+12.5=0 | | 21=3s-4(21-s) | | 8m^2=-16m+384 | | X(1.6)=2.5(x-3.6) | | 4+92=15 | | 9x+26=52 | | 3y+3=3x | | -1/2x-4.5=2x-3 | | 12=e^2x | | y=10+0.5 |